Salt̤anat-i Āṣafiyah ke Dīvān Ḥaidar Yār Ḵẖā̄ṉ Sher Jang ke muḵẖtaṣar ḥālāt - T̤ālib, Muḥammad Sirājuddīn (SAMP early 20th-century Indian books project, 1932)
On the life of Ḥaidar Yār Ḵẖāṉ Sher Jang, ruler of Hyderabad Princely State.